Analisis Sistem Sanitasi Drainase Daerah Bantaran Sungai (Studi Kasus : Gampong Garot, Darul Imarah, Aceh Besar) - Safriza Putra; Didit Wahyudi; Irin Caisarina (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2026)
The riverbank area of Garot Village, Darul Imarah District, Aceh Besar Regency, is highly susceptible to annual flooding due to its relatively low topography, high settlement density, and inadequate drainage sanitation management. This study aims to analyze the drainage sanitation management system, identify the condition of drainage facilities and infrastructure, and formulate strategies for addressing drainage-related problems in the riverbank area of Garot Village. A qualitative approach employing thematic analysis was adopted through field observations, documentation, and interviews with village officials.